Math and Arithmetic
Algebra
Calculus

# What is X squared equals 3X?

012 ###### 2013-01-10 16:21:07

It is a quadratic equation in X.

🎃
0
🤨
0
😮
0
😂
0

## Related Questions 3x squared - x squared = 2x squared 9x2 + 3x / 3x equals (3x + 1).9x2 + 3x divided by x is 9x + 3 , and then divided by 3 yields the 3x +1.   x2+3x = 7 x2+3x-7 = 0 Using the quadratic equation formula:- x = -4.541381265 or x = 1.541381265 since y = 3x+1 we have y squared =(3x+1) squared x^2 + y^2 = 25 x^2 + (3x+1)^2=25 x^2 + 9x^2+ 6x+1 = 25 10x^2 + 6x + 1 = 25 10x^2 + 6x -24 = 0 solve x from quadratic formula x = 1.28 y = 3x + 1 = 4.83 (3x - 2)(x + 1) are the factors if the equation equals 0, making x = two-thirds or -1.  3X = x2 - 2xsubtract 3X from each sideX2 - 5X = 0factor out an XX(X - 5) = 0=========X = 0--------orX = 5--------   It is a quadratic equation in the variable x. The points of intersection of the equations 4y^2 -3x^2 = 1 and x -2 = 1 are at (0, -1/2) and (-1, -1) (3x2 - 6x)/3x = 3x(x-2)/3x = x-2, for x&lt;&gt;0  3x = -111 x = -111 / 3 x = -37 x2 + x = (-37)2 - 37 = 1369 - 37 = 1332       It is a quadratic equation and its solutions are: x = -3/2 and x = 3 If x equals 8, then 3x equals 24. 24-x would equal 16. (x^2-2) (x^2+3x+5)= x^2(x^2+3x+5) -2(x^2+3x+5)= x^4 +3x^3 +5x^2 -2x^2 -6x -10= x^4 +3x^3 +3x^2 -6x -10

###### Math and ArithmeticAlgebra Copyright © 2020 Multiply Media, LLC. All Rights Reserved. The material on this site can not be reproduced, distributed, transmitted, cached or otherwise used, except with prior written permission of Multiply.